PTH-008 "real-world", single-centre experience with over-the-scope clip placement. (17th June 2017) - Smart, H; Haslam, N; Young, A
Abstract : Introduction: Over-the-scope clip (OTSC) application is indicated for the management of perforations, leaks, fistulas and gastrointestinal bleeding. We present our "real world" experience of the outcome of this technique in a variety of indications. Method: Procedures were performed under moderate sedation or propofol using either a diagnostic (Olympus H260 or HQ290) or therapeutic (Olympus 1 T240 or 2 T240) gastroscope. The OTSC clip (Ovesco Endoscopy) or the Padlock clip (Diagmed Healthcare) was employed. Depending upon indication, tissue was acquired by either suction alone or the use of various accessories (OTSC Tissue Anchor or OTSC Twin Grasper, Ovesco Endoscopy) to enable OTSC deployment. Results: All patients undergoing an OTSC procedure were recorded prospectively in an Excel spreadsheet and their outcomes analysed retrospectively after interrogation the hospital clinical, laboratory and endoscopy systems. A total of 16 patients (11 female) mean age 63.2 (range 24–78) years underwent 19 OTSC applications from June 2013 until September 2016. The median follow up was 192 (range 12–1294) days. The site, indication and outcomes are shown in the table. There were 6 deaths; median survival 47.5 (range 12–99) days. Deaths were in patients with aero-digestive (4) or post PEG (1) fistulae and spontaneous oesophageal perforation (1) despite adequate treatment. Conclusion: In our centre the commonest indication for OTSC was fistula management. Although initial success in closure was high, recurrence was common (40%). All patients with an aero-digestive fistula had successful closure; however, all but 1 succumbed to their underlying disease, stressing the difficult management challenge of such cases. Disclosure of Interest: None Declared